(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2020)
This study aimed to determine Status of Drinking Water in Kastamonu City using Water Quality Index, Ammonia, Iron, Phosphate and Manganese of drinking water quality in kastamonu City-Turkey. For this purpose, Data collection based on the average of 120 of water samples were taken either at station (before treatment), or from station (after treatment) in kastamonu city between (2011-2015). The average concentrations of the Physicochemical Parameters Water in the kastamonu city (before and after treatment) for (ammonia (NH4-N), phosphate (PO4-P), iron (Fe) and magnesium Mn) averaged between (0.0313-0.026. 0.0522-0.0331 ,0.0473-0.0233 ,0.0512-0.0262 mg/l) respectively. Findings display that the physical and chemical quality (NH4-N, PO4-P, Fe and Mn) were considerably below the Turkish Water Pollution Control Regulation (WPCSR) and USEPA standards for drinking water quality in both station. The Water quality index (WQI) is valuable and special ranking to depict the average water quality status. The Water quality index shows that the (before treatment) a higher (WQI) of 31.50 at Good water quality grades as against 17.18 at Excellent water quality grades recorded in (after treatment) in drinking water of kastamonu city the results indicated the Situation of drinking water in kastamonu city was high quality.